GROWTH PERFORMANCE OF DIPTEROCARP SPECIES PLANTED ON ABANDONED MINING AREA IN SOUTHERN THAILAND - Jetsada Wongprom (BIOTROPIA, 2020)
Dominant Dipterocarp trees hold a significant importance in the ecology and economics of the declining tropical forests of Asia. Of equal importance is the restoration of these Dipterocarp forest using the technique of matching species with silvicultural practices. The study aimed to investigate the effect of the Acacia mangium nurse trees on the survival and growth of six Dipterocarp species planted on abandoned mining areas in the Phangnga Forestry Research Station, Thailand, namely; Dipterocarpus alatus Roxb., Dipterocarpus gracilis Blume, Hopea odorata Roxb., Shorea gratissima (Wall. ex Kurz) Dyer, Shorea roxburghii G. Don, and Parashorea stellata Kurz. The approximately 1.5-year-old Dipterocarp seedlings were planted at a 6-year-old A. mangium plantation cover and at open plots. The survival rate, diameter at root collar (D0), total height (H) and the relative growth rate (RGR) of D0 and H of the seedlings were compared. Soil samples at the open and the A. mangium plots were collected and its physical and chemical properties were analyzed. The results indicated that the survival rates of the Dipterocarps planted at the A. mangium plot were higher than those at the open plots. The survival rates (75-100%) of the 1 to 3-year-old D. alatus, H. odorata, S. gratissima, S. roxburghii, and P. stellata were relatively high at the A. mangium plot, but not for D. gracilis. The D0 of S. roxburghii, D. alatus, H. odorata, and P. stellata were higher at the A. mangium plot. However, the D0 and H of S. roxburghii, D. alatus, and H. odorata at the open plot were high and similar to that of the A. mangium plot. RGRD0 and RGRH of S. roxburghii, D. alatus, and H. odorata were high both at the A. mangium and the open plots. Generally, the Dipterocarp seedlings were growing better under the A. mangium nurse trees, thus suggesting the possibility of their improved survival and growth in mined out areas. Moreover, the findings also suggest that S. roxburghii, D. alatus, and H. odorata can be planted at open areas with poor soil conditions and extreme environments. Lastly, thinning interventions are also needed to improve the growth of Dipterocarp trees.